Relationship characteristic of midwife in pregnancy services and patient satisfaction In Public Health Center, Soreang, Bandung - Balkis Fitriani Faozi; Merry Wijaya; Hadyana Sukandar (Alma Ata University Press, 2022)
Background: Pregnancy/Antenatal Care (ANC) services are the main factors in determining delivery outcomes including early detection of risk factors and also determining early treatment for pregnant women who experience complications during pregnancy. The quality of quality pregnancy services depends on the characteristics of health workers who provide services, the characteristics consist of age, educational qualifications, training and length of work.Objectives: This study aims to analyze the relationship between the characteristics of midwives in pregnancy services and patient satisfaction.Methods: This study used a cross-sectional analytical research design, namely the measurement of independent and dependent variables at the same time. The sample in this study were all midwives who worked at the Soreang District Health Center, namely 18 midwives. The midwives studied conducted examinations of 8 patients each for each pregnancy examination. Data collection techniques were carried out by filling out patient satisfaction questionnaires by pregnant women and observing pregnancy services by trained personnel using a pregnancy service checklist sheet. Furthermore, the data were analyzed by chi square test and multivariable multiple logistic regression analysis.Results: The results showed that there was a correlation between the characteristics of midwives and pregnancy services, namely the training indicator in a bivariable manner significantly affected the overall pregnancy service with a p-test of 0.007. Waiting time has a negative correlation with physical examination, laboratory, counseling and overall antenatal care with a p value of 0.002. Multivariable analysis showed that the characteristics of midwives that most influenced pregnancy care were age with p-value 0.040 [POR 1.83(1.028-3.259)], training with p-value 0.019 [POR 2.6(1.168-5.741)]. There is no relationship between pregnancy services and patient satisfaction with a p value of 0.796.Conclusion: In pregnancy services, the most influencing factors are age and training carried out by midwives. There is also a negative correlation between waiting time with physical and laboratory examinations, namely the longer the waiting time, the less physical examination services provided by midwives to patients. There is no relationship between pregnancy services and patient satisfaction.